(untitled) (Foro de Educacion, 2025)
The advancement of modern technology has accelerated the emergence of the metaverse, allowing it to surpass physical constraints and facilitate the distribution and exchange of high-quality educational content. This progression has generated growing interest in integrating metaverse technology within the domain of higher education. Although scholarly attention to this field is increasing, the majority of existing research centres predominantly on user experience within metaverse-enhanced educational settings. However, there remains a marked deficiency in literature that explores the developmental and structural design of metaverse platforms. Therefore, the present study seeks to examine metaverse modelling in higher education, with particular focus on theoretical underpinnings and system architecture. This investigation adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol to carry out a systematic review. Relevant publications were sourced from the Web of Science (WoS) and Scopus databases, specifically targeting studies concerning the utilisation of the metaverse in higher education contexts. Out of the initial literature pool, eight studies satisfied the inclusion criteria and were subjected to detailed examination. Analysis of these works identified nine fundamental elements integral to metaverse modelling in higher education: Infrastructure, Immersive Technologies, Interaction, Access Equipment, 3D Learning Scenario, Learning Task, Instructional Design, Pedagogy, and Associated Theories. This study underscores a substantial gap in research relating to the design and development aspects of metaverse applications in higher education. It is recommended that future inquiries prioritise these dimensions to facilitate the creation of robust models and conceptual frameworks that underpin effective pedagogical practices in metaverse-supported learning environments.